2009
DOI: 10.1105/tpc.109.066670
|View full text |Cite
|
Sign up to set email alerts
|

The Multifunctional Enzyme CYP71B15 (PHYTOALEXIN DEFICIENT3) Converts Cysteine-Indole-3-Acetonitrile to Camalexin in the Indole-3-Acetonitrile Metabolic Network ofArabidopsis thaliana   

Abstract: Accumulation of camalexin, the characteristic phytoalexin of Arabidopsis thaliana, is induced by a great variety of plant pathogens. It is derived from Trp, which is converted to indole-3-acetonitrile (IAN) by successive action of the cytochrome P450 enzymes CYP79B2/B3 and CYP71A13. Extracts from wild-type plants and camalexin biosynthetic mutants, treated with silver nitrate or inoculated with Phytophthora infestans, were comprehensively analyzed by ultra-performance liquid chromatography electrospray ionizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
246
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 214 publications
(252 citation statements)
references
References 61 publications
4
246
1
1
Order By: Relevance
“…Only proper identification of the carboxypeptidase will allow complete elucidation of the camalexin biosynthesis puzzle. Bö ttcher et al (2009) demonstrated the presence of g-Glu-Cys (IAN)-Gly, g-Glu-Cys(IAN), Cys(IAN), and dihydrocamalexic acid in AgNO 3 -induced Arabidopsis plants. This set of compounds corresponds to all possible intermediates in the pathway from IAN to camalexin except for Cys(IAN)-Gly.…”
Section: Involvement Of Carboxypeptidasesmentioning
confidence: 98%
See 4 more Smart Citations
“…Only proper identification of the carboxypeptidase will allow complete elucidation of the camalexin biosynthesis puzzle. Bö ttcher et al (2009) demonstrated the presence of g-Glu-Cys (IAN)-Gly, g-Glu-Cys(IAN), Cys(IAN), and dihydrocamalexic acid in AgNO 3 -induced Arabidopsis plants. This set of compounds corresponds to all possible intermediates in the pathway from IAN to camalexin except for Cys(IAN)-Gly.…”
Section: Involvement Of Carboxypeptidasesmentioning
confidence: 98%
“…Subsequently, CYP71A13 converts the aldoxime to IAN (Nafisi et al, 2007), which, after an unknown activation step, is conjugated to the tripeptide glutathione (g-Glu-Cys-Gly) by glutathione Stransferases, including GSTF6 (Bö ttcher et al, 2009;Su et al, 2011). The glutathione conjugate g-Glu-Cys(IAN)-Gly is then hydrolyzed by two consecutive peptidase reactions (discussed in detail below) to Cys(IAN), which is finally converted to camalexin by a two-step reaction catalyzed by CYP71B15 (PAD3) (Zhou et al, 1999;Schuhegger et al, 2006;Bö ttcher et al, 2009) (Figure 1). …”
Section: The Camalexin Biosynthetic Pathwaymentioning
confidence: 99%
See 3 more Smart Citations